From Metrics to Sustainability: Internationalization Practices of Higher Education Institutions in Northern Luzon, Philippines - Cipriano Jr Mendoza (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: In response to an increasingly interconnected global landscape, Higher Education Institutions (HEIs) are continuously advancing their connections and responsiveness through pursuing internationalization. This study investigates the operationalization of internationalization practices within public and private HEIs in Northern Luzon, Philippines, focusing on the core dimensions that facilitate institutional resilience and global competitiveness. Methodology: Adopting exploratory multiple-case study design, this study investigated internationalization practices across seven purposively selected HEIs in Northern Luzon, Philippines. Data triangulation involved semi-structured key informant interviews with high-level administrators, specifically, vice presidents, directors and leads of International Relations Offices (IROs), and a comprehensive document review through Thematic Analysis. These institutions were selected based on their sustained performance and upward Global ranking trajectories, providing a high-performance context for analyzing best practices in global integration. Main Findings: The findings indicate that regional HEIs utilize a strategic selectivity approach, emphasizing high-impact international memberships and trust-based partnerships as the primary drivers for sustaining mobility, collaborative research, and transnational education. These practices are integrated into the fundamental structure of the institution through a decentralized soft infrastructure, which includes specialized international centers and virtual exchange platforms that add global standards to the local curriculum while preserving indigenous knowledge intact. This operational approach ultimately enables a shift from a focus on quantitative metrics to a socially responsible, resource-aligned framework that democratizes global competence for students. Novelty/Originality of this study: This study addresses a critical gap in internationalization literature by employing multi-case study research design to investigate underrepresented public and private HEIs in Northern Luzon, Philippines. Through this, the study captures diverse spectrum of internationalization practices offering evidence-based roadmap for regional HEIs to align capacity with global standards. It provides a novel methodological framework for understanding how localized institutions transition into active participants in global knowledge exchange.